2022
DOI: 10.1128/jcm.02187-21
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Outcomes of Treated and Untreated C. difficile PCR-Positive/Toxin-Negative Adult Hospitalized Patients: a Quasi-Experimental Noninferiority Study

Abstract: Clostridioides difficile infection (CDI) is routinely diagnosed by PCR, with or without toxin enzyme immunoassay testing. The role of therapy for positive PCR and negative toxin remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Further study is needed to determine how often patients with NAAT+/TOX− results categorized as having probable or possible CDI improve without CDI treatment. Although a recent report suggested that it may be safe to withhold treatment for select hospitalized NAAT+/TOX− individuals, 8 some of these patients may have severe, complicated infections. 5,6 Bignardi et al 9 reported that 9% of glutamate dehydrogenase–positive but toxin-negative patients had persistent or recurrent diarrhea and subsequently were diagnosed with CDI based with a positive toxin test.…”
Section: Discussionmentioning
confidence: 99%
“…Further study is needed to determine how often patients with NAAT+/TOX− results categorized as having probable or possible CDI improve without CDI treatment. Although a recent report suggested that it may be safe to withhold treatment for select hospitalized NAAT+/TOX− individuals, 8 some of these patients may have severe, complicated infections. 5,6 Bignardi et al 9 reported that 9% of glutamate dehydrogenase–positive but toxin-negative patients had persistent or recurrent diarrhea and subsequently were diagnosed with CDI based with a positive toxin test.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to a recent study assessing outcomes for untreated patients with PCRþ/Tox−, which found noninferiority for unresolved diarrhea at 7 days and 30-day all-cause mortality. 5 For facilities where the microbiology laboratory tests by a molecular method and for the presence of toxin production, indeterminate (PCRþ/Tox−) results represent a significant potential for ASP to reduce inappropriate antibiotic use given that C. difficile therapy (eg, oral vancomycin) may have unintended sequelae due to its impact on the human intestinal microbiota. 6 However, clinical review is essential to ensure that appropriate patient populations are targeted to avoid missing treatment given that 43% of indeterminate cases in this study were considered true infections.…”
Section: Discussionmentioning
confidence: 99%
“…As per the European guidelines for patients with evidence of C. difficile but negative toxin test results, patients need to be evaluated clinically as they may have undetectable toxin levels or false negative toxin results or may be potential carriers of toxigenic C. difficile (Crobach et al, 2016). Hogan et al (2022) observed similar clinical outcomes in treated and untreated C. difficile NAATpositive/toxin-negative adult hospitalized patients. These data support the view that a positive direct toxin test is more closely related to infection than a positive toxin gene test.…”
Section: Higher Fecal Calprotectin Levels May Indicate Detectable Tox...mentioning
confidence: 99%